What's new in estrogen receptor action in the female reproductive tract. (19th November 2015) - Hewitt, Sylvia C; Winuthayanon, Wipawee; Korach, Kenneth S
Abstract : Estrogen receptor alpha (ERα) is a critical player in development and function of the female reproductive system. Perturbations in ERα response can affect wide-ranging aspects of health in humans as well as in livestock and wildlife. Because of its long-known and broad impact, ERα mechanisms of action continue to be the focus on cutting-edge research efforts. Consequently, novel insights have greatly advanced understanding of every aspect of estrogen signaling. In this review, we attempt to briefly outline the current understanding of ERα mediated mechanisms in the context of the female reproductive system.